Complications in liposuction: systematic review - Luiz Fernando Lima Barros; Vinícius Fialho Teixeira; José Augusto Púpio Reis; Rebeca Andrade Ferraz; Dinéia da Conceição Araújo; Fabiel Spani Vendramin (Revista Brasileira de Cirurgia Plástica, 2023)
Liposuction is among the most performed plastic surgery procedures in Brazil. According to data from the International Society of Aesthetic Plastic Surgery (ISAPS), 231,604 liposuctions were performed, 15.5% of all aesthetic procedures in the country in 2019. Adopting liposuction as a single procedure or adjunct to other cosmetic procedures stimulated its technical evolution from simple fat aspiration to more sophisticated body shaping. Thus, this review aimed to systematically evaluate the published data regarding the complications found in liposuction. A review was conducted using PubMed, SciELO, LILACS, Cochrane Library, SCOPUS, Web of Science, and gray literature databases, published between 2016 and 2021, using the descriptors “Liposuction” and “Complications.” A total of 187 articles were found in the searched databases, of which 16 were selected according to the outcome “to assess safety through the prevalence of complications in liposuction as a single procedure and associated with other procedures such as abdominoplasty and fat grafting.” We found a mortality rate ranging from 0 to 0.06 among all procedures and a predominance of venous thromboembolism, hematoma, seroma, and hyperpigmentation concerning all complications, being more common when liposuction is associated with other procedures. Therefore, through this review, it was possible to verify that liposuction as a single procedure has lower complication rates when compared to liposuction combined with other procedures.